2018
DOI: 10.1186/s12943-018-0921-y
|View full text |Cite
|
Sign up to set email alerts
|

LncHOXA10 drives liver TICs self-renewal and tumorigenesis via HOXA10 transcription activation

Abstract: BackgroundLiver cancer is one of the most deadly cancers in the world. There are various cells in liver tumor bulk, including liver tumor initiating cells (TICs), which account for liver tumorigenesis, drug resistance, relapse and metastasis. The homeobox (HOX) transcription factors play critical roles in many physiological and pathological processes, while, their roles in liver TICs and liver tumorigenesis remain unknown.MethodsAn unbiased screening was performed using online-available datasets. Liver TICs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Mechanistically, lncFZD6 directly binds and recruits the BRG1 (Brahma-related Gene 1 protein)-embedded the switch/sucrose non-fermenting (SWI/SNF) complex to the FZD6 promoter, which facilitates the transcription of FZD6 via chromatin remodeling [21]. Similarly, the overexpressed lncHOXA10 recruits the nucleosome remodeling factor (NURF) chromatin remodeling complex to the HOXA10 promoter to initiate the expression of HOXA10, and ultimately promotes the self-renewal of liver TICs and the progression of HCC [22]. Collectively, increasing studies have shown that lncRNAs epigenetically regulate gene transcription by manipulating DNA methylation and histone acetylation.…”
Section: Lncrnas As Novel Regulators In Hcc Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, lncFZD6 directly binds and recruits the BRG1 (Brahma-related Gene 1 protein)-embedded the switch/sucrose non-fermenting (SWI/SNF) complex to the FZD6 promoter, which facilitates the transcription of FZD6 via chromatin remodeling [21]. Similarly, the overexpressed lncHOXA10 recruits the nucleosome remodeling factor (NURF) chromatin remodeling complex to the HOXA10 promoter to initiate the expression of HOXA10, and ultimately promotes the self-renewal of liver TICs and the progression of HCC [22]. Collectively, increasing studies have shown that lncRNAs epigenetically regulate gene transcription by manipulating DNA methylation and histone acetylation.…”
Section: Lncrnas As Novel Regulators In Hcc Metastasismentioning
confidence: 99%
“…In addition, lncRNAs also mediate tumor cells that exhibit unique metabolic phenotypes, such as lncRNA TUG1 (taurine up-regulated gene 1), which exerts a master regulator to coordinate glycolysis and metastasis in HCC [71]. Furthermore, emerging findings revealed that lncRNAs can modulate the transcription of metastasis-related genes to maintain TIC self-renewal and tumor initiation capacity, such as lncSox4 [23], lncFZD6 [21], and lncHOXA10 [22]. Moreover, lncRNA HULC and MALAT1 may promote HCC metastasis via enhancing EMT and migration in the miRNAs/ZEB1 signaling [16,38].…”
Section: Role Of Lncrnas In the Multi-step Process Of Hcc Metastasismentioning
confidence: 99%
“…Hoxa10, a member of the homeobox gene family, can participate in the development and growth of multiple systems, as indicated by its critical roles in male and female fertility, liver tumorigenesis, gastric cancer invasion and leukemogenesis. [55][56][57][58] Moreover, multiple lines of evidence have shown that Hoxa10 is necessary for the global patterning of the mammalian skeleton. [59][60][61] Furthermore, Hoxa10 can promote osteoblast differentiation through the activation of Runx2 and directly regulate osteoblast differentiation genes, including the alkaline phosphatase, osteocalcin, and bone sialoprotein genes, and this process can be regulated by the Pbx1 complex.…”
Section: Discussionmentioning
confidence: 99%
“…HOXA10 also takes an important part in embryo implantation [7], endometriosis [8]and hematopoietic lineage commitment [9]. Importantly, HOXA10 is involved in a wide spectrum of biological functions in human cancers, including hepatocellular carcinoma [10,11], lung cancer [12], gastric cancer [13], bladder cancer [14], as well as glioma [15]. However, the expression and role of HOXA10 in CRC has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…The knockdown of LincHOXA10 expression was shown to induce glioma cell apoptosis [24]. Shao et al found that LincHOXA10 drives liver tumor initiating cells (TICs) self-renewal and tumorigenesis [11]. However, the function and underlying mechanism of LincHOXA10 in the development of CRC remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%